PENGGUNAAN MEDIA BALOK ANGKA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF ANAK KELOMPOK B TAMAN KANAK-KANAK - Wa Sandi Baidin; Rosmarin Tutupary; Junita. L. Kundre (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study addresses the low cognitive abilities of Kelompok B children at TK Nurul Iman in understanding number symbols, sequencing numbers, and matching quantities to corresponding symbols. The problem stems from limited learning media and an overreliance on verbal instruction, which reduces children’s engagement and focus. The research aims to determine whether the use of number block media can enhance the cognitive development of these children. Employing a Classroom Action Research design based on the Kemmis and McTaggart model, the study was conducted in two cycles, each comprising planning, action, observation, and reflection. The subjects were 25 children aged 5–6 years. Data were collected through systematic observation and documentation, then analyzed using percentage techniques to assess developmental indicators. The results revealed a significant improvement across both cycles. In Cycle I, 48% of the children remained in the “Not Yet Developed” category, indicating persistent difficulties in number recognition and problem-solving. After implementing targeted improvements in Cycle II, such as clearer demonstrations, structured group activities, and step-by-step practice, the outcomes shifted dramatically: 0% remained in the “Not Yet Developed” category, 8% were “Beginning to Develop,” 16% “Developed as Expected,” and 76% reached “Very Well Developed.” These findings demonstrate that number block media effectively stimulate logical thinking, number symbol recognition, and independent problem-solving in early childhood. Consequently, the integration of concrete, manipulative media like number blocks is highly recommended for optimizing cognitive development in early childhood education settings.